La evaluación de las actividades musicales - Rafael Prieto Alberola (Universidad de La Rioja, 2013)
After establishing and reflecting on some of the conditions which complicate evaluation tasks in general and musical evaluation in particular, the writer of this article revises some of the established models and finally suggests various criteria which facilitate the evaluation of musical activities.